Multi-objective optimisation of building design variables and its impact on office building performance: a case for Ghana - Adjei, Eunice Akyereko (2015)
Multi-objective optimisation of building design variables is an appropriate and robust approach in assessing office building performance. Conversely, in developing country contexts like Ghana there is lack of credible building design variables from scientific and technical journals. The main research problem was low building performance assessment by building professionals in Ghana resulting in high cooling energy utilization and indoor environmental discomfort within the commercial building sector. Overall, the aim of the research was to use cost effective low energy technologies to optimize the building design variables to achieve recommended good practice for energy utilization of service equipment and indoor environmental performance in office building. Research questions addressed in this research included the following: 1. How does local building professionals’ practices impact on design variables used in performance assessment, and are occupants’ comfortable as well as satisfied with building performance in Ghana? 2. Are the building fabrics used in Ghana suitable for enhancing building performance? 3. How can the building performance design variables from survey questionnaires and experimental assessments be optimized? 4. Are the existing economic benefit assessment tools adequate for fast accurate decision making in comparing recommended good practice for cooling load by CIBSE Guides in hot-humid climate? The following creative and novel methodologies were used for this research: 1. Survey questionnaires using Bristol Online Survey Tool for the administration and acquisition of responses from participants. 2. Experimental assessment of selected fabrics from Ghana and creative parametric fabrics using both TCi Thermal Analyser and AutoPore IV mercury intrusion Porosimeter. 3. Computer simulations for optimised design variables using ESDL Tas. Finally, Design of creative comparator decision making tool for economic benefit assessment of the optimised computer simulations design variables. The selected significant findings from the application of the creative and novel methodologies in addition to the corresponding implications are summarised as follows: 1. An average of 16% of all building professionals do assess design variables associated with its practices with about 60% building professionals satisfied with Ghana building regulations, on the contrary, highly recommended for an improvement on the regulations. 2. Experimental assessment of representative selected Ghana building fabrics and enhanced parametric studies meets the thermo-physical properties outlined in the CIBSE Guide standards, with the range of thermal conductivity being 0.2 to 0.7W/m2K. 3. From the creative computer simulation outcomes, the cooling load of the base case is about 10 times more than the recommended good cooling load practice outlined in CIBSE Guides. The optimised computer simulation single wall layer building design model was achieved using optimum low transmittance building fabrics, optimum internal conditions and low chilled beam technology. 4. From the economic benefit assessment, an increasing trend of inverse correlation between difference in modification cost with cooling load reduction was observed. That is, for reduction in cooling load, there is an increasing cost in modification. For example, for reduction of cooling load of 40% from Case 1 to Case 3, there is a corresponding increase in modification cost of 79.4%. 5. Representative office occupants are generally satisfied and comfortable with building performance in Ghana. The above findings have compounded extreme implications on the local building professionals’ practices, leading to subsequently high cooling load, hence the rising energy utilization of service equipment in non-residential buildings. Finally, the overall aim of achieving the recommended good practice for service equipment energy utilization in commercial buildings was not accomplished for the cooling load. This is due to the difference in cooling load calendar used by CIBSE Guide and hot-humid climate, Ghana. In conclusion, an optimised low cost computer simulation of single wall layer envelope design, with cooling load of 120 kW/m2 for floor area and acceptable indoor environmental quality has been achieved in this research. It is strongly, recommended that, performance assessment should be incorporated into building permit issuing process using the designed creative feedback chart designed in this research.